2013
DOI: 10.5172/conu.2013.45.1.126
|View full text |Cite
|
Sign up to set email alerts
|

A good day in nursing: Views of recent Singaporean graduates

Abstract: This paper arises from the analysis of data from a large Singapore-based survey and a complementary qualitative series of 17 individual interviews. Some results from both arms of the research have been previously analysed and are reported elsewhere. Answers to a series of questions within the questionnaire and the structured interviews have been drawn together under the umbrella of investigating of recent Singaporean graduates' views about the characteristics of a good nurse, a good day at work, and how they u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…These nurses previously provided consent to be contacted for future research and were sent a survey [survey results are reported in companion papers (Cleary et al . , b)]. At the end of the survey, respondents were able to state whether they wished to be contacted for the purpose of a face‐to‐face interview.…”
Section: Methodsmentioning
confidence: 99%
“…These nurses previously provided consent to be contacted for future research and were sent a survey [survey results are reported in companion papers (Cleary et al . , b)]. At the end of the survey, respondents were able to state whether they wished to be contacted for the purpose of a face‐to‐face interview.…”
Section: Methodsmentioning
confidence: 99%
“…In Singapore, the nursing profession is predominantly female, there is a shortage of registered nurses (RN), and the nursing workforce has a strong work ethic, typically working long hours to meet tight deadlines (Cleary et al ., ,b). According to Gantz et al ., (), Singapore has a younger nursing workforce than in most developed countries, and there is substantial attrition of nurses within the first three years of their career related to the less‐than‐ideal working environment.…”
Section: Introductionmentioning
confidence: 99%
“…The concept that RNs are trying to do the right thing is not just limited to the boundaries of this study. There is discourse throughout the literature that relates to RNs doing the right thing (Catlin, 2013;Dee, & Endacott, 2011;Cleary, Horsfall, Muthulakshmi, & Jackson, 2013;Horton-Deutsch et al, 2014;Newham, 2015). The literature revealed that there is an expectation that RNs do the right thing professionally, morally and ethically (Holt & Convey, 2012;Smith & Godfrey, 2002;Tuckett, 1998).…”
Section: Discussionmentioning
confidence: 99%